Dynamic fracture behaviour in fibre-reinforced cementitious composites. (August 2016) - Yu, Rena C.; Cifuentes, Héctor; Rivero, Ignacio; Ruiz, Gonzalo; Zhang, Xiaoxin
Abstract: The object of this work is to simulate the dynamic fracture propagation in fibre-reinforced cementitious composites, in particular, in steel fibre reinforced concrete (SFRC). Beams loaded in a three-point bend configuration through a drop-weight impact device are considered. A single cohesive crack is assumed to propagate at the middle section; the opening of this crack is governed by a rate-dependent cohesive law; the fibres around the fracture plane are explicitly represented through truss elements. The fibre pull-out behaviour is depicted by an equivalent constitutive law, which is obtained from an analytical load–slip curve. The obtained load–displacement curves and crack propagation velocities are compared with their experimental counterparts. The good agreement with experimental data testifies to the feasibility of the proposed methodology and paves the way to its application in a multi-scale framework. Abstract : Highlights: The first work in considering explicitly fibre distribution, fibre–concrete interface failure in dynamic fracture of steel fibre reinforced concrete. A novel form of cohesive law accounting for the rate-dependency of concrete in dynamic fracture. A multi-scale framework is established for modelling cohesive crack propagation in fibre-reinforced composites.